2021
DOI: 10.1186/s12967-021-02714-8
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical model of health management using data-driven decision-making: the future of precision medicine and health

Abstract: Background The burden of chronic and societal diseases is affected by many risk factors that can change over time. The minimalisation of disease-associated risk factors may contribute to long-term health. Therefore, new data-driven health management should be used in clinical decision-making in order to minimise future individual risks of disease and adverse health effects. Methods We aimed to develop a health trajectories (HT) management methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 43 publications
0
7
0
1
Order By: Relevance
“… 39 More studies have found that precision medicine is the key to improving ccRCC outcomes; however, because of the lack of reliable biomarkers, precision medicine is severely limited in the treatment of ccRCC. 40 , 41 , 42 Exosomes have the advantages of easy availability, non‐invasive examination, and tumor specificity. 24 Meanwhile, due to their high mobility and lipid bilayer structure, they can easily passthrough biological membranes and protect rich bioactive substances present inside the membranes from degradation.…”
Section: Discussionmentioning
confidence: 99%
“… 39 More studies have found that precision medicine is the key to improving ccRCC outcomes; however, because of the lack of reliable biomarkers, precision medicine is severely limited in the treatment of ccRCC. 40 , 41 , 42 Exosomes have the advantages of easy availability, non‐invasive examination, and tumor specificity. 24 Meanwhile, due to their high mobility and lipid bilayer structure, they can easily passthrough biological membranes and protect rich bioactive substances present inside the membranes from degradation.…”
Section: Discussionmentioning
confidence: 99%
“…In healthcare, decision support systems are signi cantly important to both the providers and the patients 38,39 . Effectively reducing time management by supporting the decision-making for clinicians will eventually provide high-quality care and drive the right clinical outcomes for the patients 40,41 . Therefore, implementing an accurate but deeper analysis system of interpreting the risk predictors to improve the decision-making prior to an event plays a crucial role in anticipating the patient's stay.…”
Section: Discussionmentioning
confidence: 99%
“…In healthcare, decision support systems are signi cantly important to both the providers and the patients [38,39]. Effectively reducing time management by supporting the decision-making for clinicians will eventually provide high-quality care and drive the right clinical outcomes for the patients [40,41]. Therefore, implementing an accurate but deeper analysis system of interpreting the risk predictors to improve the decision-making prior to an event plays a crucial role in anticipating the patient's stay.…”
Section: Substantial Findingsmentioning
confidence: 99%